Molecular Profiling of Multidrug-Resistant Zoonotic Shigella spp. in Chicken Farms: A Case Study from Diyala - Al-Shattrawi, Huda Jihad G. (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Zoonotic bacterial infections caused by multidrug-resistant (MDR) strains pose a growing global public health concern, particularly through the food chain from poultry to humans. The emergence of resistant Shigella species in poultry farms has heightened the risk of zoonotic transmission and complicates treatment options. Aims: This review aims to synthesize current knowledge on the prevalence, virulence factors, and antimicrobial resistance profiles of Shigella spp. isolated from poultry, with a focus on their potential for zoonotic transfer and public health impact. Methods: A systematic literature review was conducted by searching major scientific databases (e.g., PubMed, Scopus) using specific keywords related to Shigella, poultry, antimicrobial resistance, and zoonosis. Selected studies were evaluated for epidemiological data, molecular characterization, and resistance patterns, and data were analyzed qualitatively to identify common themes and gaps. Results: The review identified a notable prevalence of Shigella spp. in poultry farms, with many isolates harboring key virulence genes such as virA, sat, ial, set1A, and set1B. A significant proportion exhibited multidrug resistance, especially against antibiotics like ampicillin and tetracycline, raising concerns about zoonotic transmission and treatment challenges. Novelty: This review is among the first to compile and analyze molecular and resistance profiles of MDR Shigella spp. directly from poultry sources in the Middle East, highlighting their critical zoonotic potential and resistance trends in this region. Implications: The findings emphasize the urgent need for stricter antibiotic stewardship, improved farm biosecurity, and continuous surveillance to monitor and control the spread of resistant Shigella strains from poultry to humans. Such measures are essential to mitigate public health risks and curb the escalation of antimicrobial resistance. Highlights: High MDR Prevalence: Shigella spp. isolated from poultry frequently show resistance to multiple antibiotics, complicating treatment options. Virulence Risk: Presence of virulence genes (e.g., virA, set1A/B) highlights their zoonotic potential and health impact. Regional Insight: This is among the first reviews highlighting MDR Shigella in poultry from the Middle East, filling a key knowledge gap. Keywords: Zoonotic, Shigella spp., Molecular, Chicken Farms, Multi-Drug Resistant